APPLICATION OF MULTITUDE THEORY ELEMENTS IN EDUCATIONAL PROJECTS - Кадильникова, Т. М.; Лазарєва, Є. Д. (Proceedings of the National Aviation University. Series: Pedagogy, Psychology, 2015)
The article analyzes the results of the research of a system of dynamic factors, that determine product quality of an educational project in university. On the basis of theoretical researches the model of evaluation of product quality of an educational project stressing the place allocated to innovative technologies was developed and described. Based on mathematical processing of experimental results statistical forecasting methods were proved. Adequate models for determining the main components of the index competencies of users of educational projects, that make it possible to create a fundamental approach to the estimation of quality of the product within the fixed rate of resource support for its further selection to the educational program, were obtained